Treatment of Tourette Syndrome - Kurlan, Roger M. (Springer US, 2013)
Tourette’s syndrome (TS) consists of chronic motor and phonic tics and characteristically begins in childhood. The tics can be disabling and commonly associated behavioral comorbities such as attention deficit hyperactivity disorder (ADHD) and obsessive-compulsive disorder (OCD), can also cause problems in daily functioning. The underlying etiology and neurobiology of TS remain unknown although genetic factors appear to be important, cortical control of basal ganglia motor function appears to be disturbed and neurochemical abnormalities, particularly involving dopamine neurotransmission, are likely present. The treatment of TS involves appropriate education and support. Tics can be treated with habit reversal cognitive behavioral therapy, medications (most commonly alpha agonists and antipsychotics), local intramuscular injections of botulinum toxin and some severe, refractory cases have responded to deep brain stimulation surgery (DBS). It is important to appropriately diagnose and treat comorbid behavioral disorders that are disrupting function. OCD can be treated with cognitive behavioral therapy, selective serotonin reuptake inhibitors, and atypical antipsychotics. DBS has become a treatment option for patients with disabling OCD despite other therapies. ADHD is treated with appropriate classroom accommodations, behavioral therapy, alpha agonists, atomoxetine or methylphenidate-containing stimulant drugs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-013-0215-4) contains supplementary material, which is available to authorized users.